2001
DOI: 10.5558/tfc77097-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of mixedwood stands by wintering white-tailed deer in southern New Brunswick

Abstract: On the northern edge of their range, white-tailed deer (Odocoileus virginianus) congregate during winter to cope with severe climate conditions. We documented the winter habitat use of deer in southern New Bmnswick, where winters are of moderate severity, and tested predictions concerning the influence of food and cover availability on habitat use by deer under different snow depth regimes. Sixty-three radio-collared deer were monitored during the winters of 1995 to 1997. Within wintering areas, deer showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…In the regenerated landscape, we found a nonlinear relationship between the probability of intensive use and the basal area in balsam fir, indicating that deer were more likely to use intensively areas of their home range where basal area of balsam fir was intermediate. Northern ungulates have also been reported to select forest stands with intermediate canopy cover; although this was achieved by selecting mixed-wood stands (Sabine et al 2001. Our findings reinforce the influence of fine-scale interspersion of forage and cover, as Anticosti deer reduced foraging costs by selecting for intermediate cover and high forage abundance.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the regenerated landscape, we found a nonlinear relationship between the probability of intensive use and the basal area in balsam fir, indicating that deer were more likely to use intensively areas of their home range where basal area of balsam fir was intermediate. Northern ungulates have also been reported to select forest stands with intermediate canopy cover; although this was achieved by selecting mixed-wood stands (Sabine et al 2001. Our findings reinforce the influence of fine-scale interspersion of forage and cover, as Anticosti deer reduced foraging costs by selecting for intermediate cover and high forage abundance.…”
Section: Discussionsupporting
confidence: 73%
“…com). We tested for a quadratic effect of basal area and stem density of balsam fir, because large herbivores are known to select forest stands with intermediate cover during winter (Sabine et al 2001). We used multicollinearity diagnostic statistics to verify problematic correlations between explanatory variables.…”
Section: Data Analysesmentioning
confidence: 99%
“…Despite numerous studies in mixed-forest habitat, few have identified mixed-forest species (but see Mazur et al, 1998;Robichaud and Villard, 1999;Sabine et al, 2001;Girard et al, 2004). However, there may be no particular habitat feature of mixed forests to which species are adapted that does not exist in either pure deciduous or conifer forest; mixed forest may represent a forest type in which generalists can exist alongside deciduous-and conifer-associated species.…”
Section: Introductionmentioning
confidence: 93%